Analisis Penilaian Matematika pada Materi Bilangan Cacah melalui Media Nilai Tempat Bilangan di SDN Pasar Baru 1 - Wijaya, Arman; Unaenah, Een; Akbar, Ahmad Alvinda (TSAQOFAH, 2023)
This study aims to analyze the assessment of whole number material using place value media for second grade students at SDN Pasar Baru 1. Regarding knowledge in whole number material, second grade students still need concrete objects to understand whole number material. This is what makes the obstacles that occur in class II in whole number material, class II students have difficulty determining the place of numbers, many students are not careful in writing numbers in Latin and many students do not understand using dots on numbers. Therefore, the solution to overcome these obstacles is by using place value media because it can attract students' understanding to make it easier to understand the whole number material. This type of research used is qualitative research with descriptive methods. Data collection techniques in the form of observation, interviews, documentation and tests. The research subjects were class II teachers. The results obtained in this research are that students achieve 95 and the lowest score is 50, this is important for students to increase their scores. In the assessment the teacher gives the appropriate value.